HUBUNGAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMP DI KABUPATEN BANDUNG BARAT MENGENAI MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL - LIA AWALUHUM; Ratna Sariningsih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
This study aims to describe the mathematical communication skills of seventh grade students of West Bandung District Junior High School in understanding linear equations and one variable inequality. This type of research is qualitative research. Research subjects were selected based on even semester semester math report cards. Research subjects used in this study were 3 students selected from 15 students, namely one high-ability student, one moderate-capable student and one low-ability student. The results of this study were (1) Subjects with high ability in understanding Equation and the inequality of one variable reaches three indicators of mathematical communication ability that is to state mathematical problems related to Linear Inequality and Inequality One variable in the form of a story problem. stating the problem given in the form of mathematical models in the form of equations and solving them and stating a story problem into an idea or problem related to Equality and Inequality of one variable and can solve the problem, (2) Subjects with moderate ability to understand Equations and Inequality One variable reaches two indicators of mathematical communication ability, namely expressing mathematical problems related to equations and inequality of one variable in the form of story problems and expressing an image into an idea or mathematical problem related to linear equations and inequalities of one variable and the problem can be solved. And (3) Subjects with low ability in understanding Equations and inequality of one variable reach an indicator of mathematical communication ability which states mathematical problems related to linear equations and inequalities of one variable.